Methodology of Planning Tax Expenses - Safonova, Margarita Fridrihovna; Kalinina, Irina Nikolaevna; Vasilieva, Nadezhda Konstantinovna; Bershitskiy, Yuriy Iosifovich; Kiselevich, Tatiana Ivanovna (International Journal of Economics and Financial Issues, 2016)
The article considers the issue related to the necessity to create a unified approach to planning tax expenses of the organization. Ways to minimize taxation burden are analyzed, and variants to plan tax expenses are systemized. Taking into account the increasing social responsibility of economic entities under conditions of the economic crisis, it was required to transform the goal of the taxation strategy of organizations to the model of tax expenses optimization. The approach to planning tax expenses developed by the authors is based not on the model of the tax minimization but on the shift of emphasis of tax expenses optimization that allows economic entities to more efficiently use financial resources taking into account the current legislation, as well as to achieve long-term goals of the business development strategy. In the work this task is solved by expanding the essential area of defining tax expenses planning. Theoretical importance of the article is in the fact that the research of tax expenses is based on theoretical basics of micro-economy, as well as considerable provisions of the current Russian legislation. Keywords: tax expenses, taxation planning, taxation burden, efficiency of taxation strategy, internal control. JEL Classifications: H20, H21, H30